Hypothenar hammer syndrome in a computer programmer: CTA diagnosis and surgical and endovascular treatment. - Abdel-Gawad EA; Bonatti H; Housseini AM; Maged IM; Morgan RF; Hagspiel KD (Vascular & Endovascular Surgery)
Finger ischemia due to embolic occlusion of digital arteries resulting from trauma to the palmar ulnar artery has been termed hypothenar hammer syndrome (HHS). In HHS, arterial thrombosis and/or aneurysm formation with embolization to the digital arteries causes symptoms of ischemia. We describe a patient in whom the initial diagnosis was made on multidetector computed tomographic angiography (CTA), as well as his endovascular and surgical management.